Crashworthiness Investigation of Multi-stage Structures Designed for Underrun Protection Devices - Thongtip, Tongchana; Chanthanumataporn, Saharat (Applied Science and Engineering Progress, 2021)
Due to the disparity between large trucks and passenger vehicles, most deaths in large truck crashes are occupants in small cars, which under-ride the large truck. To protect the under-riding of small vehicles during crash and mitigate the severity, various designs of underrun protection devices have been developed to be installed at the front, side, rear of trucks. Not only can underrun protection devices protect a small vehicle from under-riding a truck, but also minimize the severity of crash to develop crashworthiness. In this paper, various cross section patterns of underrun protection device guard bar are designed with the aims to improve the crashworthiness. Moreover, the crashworthiness capability is clarified for future design guideline. The proposed structural configuration is designed from the concept of multi-stage energy absorption, which also results in an improvement of bending stiffness. To investigate the crashworthiness of the proposed design, the dynamic analysis is performed in LS-DYNA explicit commercial finite element analysis package. The guard bar is cut partially and investigated by performing drop impact test. Energy absorption, specific energy absorption, peak impact force, crash force efficiency, and stroke efficiency are considered as quantitative criteria for crashworthiness evaluation. The technique of order of preference by similarity to ideal solution is adopted to perform a multi-criteria decision analysis and identify the overall performance score of each design. The results indicate that the triple stage UPD guard bar yields the best performance score and improve the overall crashworthiness score up to 10% as compared with the rectangular design of standard UPD guard bar.